(untitled) (Global Journal of Human-Social Science, 2023)
Metaphysical poetry is a genre of poetry that deals with deep and profound subjects like spirituality religion etc It s a really heady kind of poetry that shows the world in a new light There are many unanswered questions raised The best examples of metaphysical poetry force the reader to question the very nature of reality itself Its imagery humour and absurdity transport the reader to a fantastical realm where new insights might be gained The final point is that metaphysical poetry requires a precise and rigorous approach to language due to the usage of sophisticated philosophical concepts and religious topics The poet has to be able to express these high-level concepts eloquently and precisely using language and grammar that leaves no room for misunderstanding Overall the ability to explain complicated concepts clearly and coherently through a rigorous style is crucial for successful metaphysical poetry